AN ANALYSIS OF TAX AVOIDANCE BY MINING COMPANIES INFLUENCED BY LIQUIDITY AND COMPANY SIZE - Yosi Nivia Ambarwati (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2025)
Penelitian ini bertujuan untuk menganalisis pengaruh Profitabilitas, Likuiditas, dan Ukuran Perusahaan terhadap Tax Avoidance yang dilakukan oleh per This study aims to analyze the effects of Profitability, Liquidity, and Firm Size on Tax Avoidance among mining companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2022 period. The sample was selected using a purposive sampling method, and based on the predetermined criteria, 30 mining companies were included in the study. Hypothesis testing was conducted using multiple linear regression analysis to examine the effect of each independent variable on Tax Avoidance. The results indicate that Profitability, as measured by Return on Assets (ROA), does not have a positive effect on Tax Avoidance. In contrast, Liquidity, as measured by the Current Ratio (CR), has a positive effect on Tax Avoidance, while Firm Size also has a positive effect on Tax Avoidance. usahaan pertambangan yang terdaftar di Bursa Efek Indonesia (BEI) pada periode 2018 s.d. 2022. Pengambilan sampel dilakukan dengan menggunakan metode purposive sampling dan berdasarkan kriteria yang telah ditentukan, diperoleh sampel sebanyak 30 perusahaan pertambangan. Pengujian hipotesis dilakukan dengan menggunakan analisis regresi linear berganda untuk mengetahui pengaruh dari masing masing variabel independen terhadap Tax Avoidance. Hasil penelitian ini menunjukkan bahwa Profitabilitas (ROA) tidak berpengaruh positif terhadap Tax Avoidance, Likuiditas (CR) berpengaruh positif terhadap Tax Avoidance, dan Ukuran Perusahaan berpengaruh positif terhadap Tax Avoidance.